Zinc-Phosphorus Complex Working as an Atomic Valve for Colloidal Growth of Monodisperse Indium Phosphide Quantum Dots - Koh, Sungjun; Eom, Taedaehyeong; Kim, Whi Dong; Lee, Kangha; Lee, Dongkyu; Lee, Young Kuk; Kim, Hyungjun; Bae, Wan Ki; Lee, Doh C. (AMER CHEMICAL SOC, 2017)
Growth of monodisperse indium phosphide (InP) quantum dots (QDs) represents a pressing demand in display applications, as size uniformity is related to color purity in display products. Here, we report the colloidal synthesis of InP QDs in the presence of Zn precursors in which size uniformity is markedly enhanced as compared to the case of InP QDs synthesized without Zn precursors. Nuclear magnetic resonance spectroscopy, X-ray photoelectron spectroscopy, and mass spectrometry analyses on aliquots taken during the synthesis allow us to monitor the appearance of metal phosphorus complex intermediates in the growth of InP QDs. In the presence of zinc carboxylate, intermediate species containing Zn-P bonding appears. The Zn-P intermediate complex with P(SiMe3)(3) exhibits lower reactivity than that of the In P complex, which is corroborated by our prediction based on density functional theory and electrostatic potential charge analysis. The formation of a stable Zn P intermediate complex results in lower reactivity, which enables slow growth of QDs and lowers the extreme reactivity of P(SiMe3)(3), hence monodisperse QDs. Insights from experimental and theoretical studies advance mechanistic understanding and control of nucleation and growth of InP QDs, which are key to the preparation of monodisperse InP-based QDs in meeting the demand of the display market.
Keywords: LIGHT-EMITTING-DIODES; INP-AT-ZNSES; PRECURSOR CONVERSION; SEMICONDUCTOR NANOCRYSTALS; INP/ZNS NANOCRYSTALS; SUPPRESSED BLINKING; MASS-SPECTROMETRY; PERFORMANCE; CDSE; CHEMISTRY